Sociofamily risk and cognitive impairment in elderly adults treated at the Geriatric Center of the Peruvian Air Force in the period 2017-2020 - De Jesús Begazo Bedoya, Mimmy Minerva (2023)
Introduction: Older adults constitute those over 65 according to the WHO. Likewise, sociofamily risk and cognitive impairment have been related in patients from the geriatric center of the Peruvian air force in the period 2017-2020. Objectives: To determine the association between socio-family risk and cognitive impairment in patients treated at the HFAP geriatric center in the period 2017-2020. Methodology: Primary, observational, analytical, cross sectional, retrospective study carried out in patients treated at the geriatric center of the HFAP in the period 2017-2020. Results: 121 older adults were evaluated, with an average age of 84 years. 23.1% presented social risk, 41.3% presented cognitive deterioration. 30.6% had type 2 diabetes mellitus and 13.2% Parkinson's disease. No significant association was found between socio-familial risk (p=0.851) and suffering from cognitive impairment. Suffering from type 2 diabetes mellitus (p=0.022) was associated with cognitive impairment. Conclusions: No association was found between socio-familial risk and cognitive impairment. It is necessary to carry out more studies in larger and more varied populations to evaluate risk factors for the development of cognitive impairment and other pathologies that affect the elderly in our country.